(untitled) (Entrepreneurship Journal for Finance and Business, 2026)
The research aims to reach the optimal management of water resources in the city of Baghdad by using the Analytic Hierachy Process - AHP, which is one of the effective methods of supporting the process of making multiple decisions. Baghdad faces many challenges related to the water sector, including a lack of water quantities available, water deterioration, institutional and administrative challenges. The research follows a comprehensive scientific methodology that begins to determine the problem, and set clear goals related to improving the effectiveness and efficiency of water management and ensuring its sustainability. Where an analytical model is built with the use of (AHP) analysis, which includes defining the main goal of (optimal water management), standards of evaluation (water pricing, awareness and aqueous education, systems and water standards, legislation and water laws, water losses), and possible alternatives (improving infrastructure Rationalizing water use). The data was collected through a questionnaire for the competent authorities and experts in the water sector exclusively. Through the AHP (AHP) application, both standards as well as alternatives and arrangement were analyzed based on the relative weights of each standard. The results show the possibility of using (AHP) to direct specialists and decision makers towards choosing sustainable and effective solutions to address water issues. And highlighting the results of the research was the possibility of access to the optimal water management in the city of Baghdad, by formulating a comprehensive water management approach by adopting a strategy to integrate school standards and alternatives, and set a maximum priority for the application of rationalization of water use as an implementable option and the first step to achieve a sustainable water resource, which supports Achieving efficiency of water resources optimall. With the presence of practical recommendations that are applicable, most notably promoting the rationalization of water use through a comprehensive work for both water legislation and awareness of users of the importance of water, as well as the need for water pricing to estimate the value of water as an important resource. The research is expected to improve the management of water resources in Baghdad, and it can also constitute an applicable model in other cities facing similar challenges.